Postmarketing withdrawal of human medicinal products because of adverse reactions in animals: a systematic review and analysis. - Onakpoya, I; Heneghan, C; Aronson, J (Wiley, 2017)
Purpose We have identified human medicinal products for which animal data were used as evidence for withdrawal, determined whether the adverse reactions were reported in humans, established whether confirmatory human studies were conducted, and explored the withdrawal patterns over time. Methods We searched the World Health Organization's Consolidated List of [Medicinal] Products, drug regulatory authorities' websites, PubMed, Google Scholar, and selected textbooks to identify medicinal products withdrawn from 1950 to June 2016. We included medicinal products for which animal data were specifically reported as a reason for withdrawal. We used a checklist adapted from the International Agency for Research on Cancer criteria to rate the evidence. Results In 37 cases, evidence from animals was the reason given for withdrawal between 1963 and 2000. Evidence of carcinogenicity was cited in 23 cases (62%). Limited evidence for harms occasioned withdrawal in over 80% of cases. In 11 cases (30%), the adverse drug reactions were subsequently reported in humans. In 5 instances (14%), formal studies were conducted in humans. The median interval to withdrawal following reports of adverse reactions was 2 years (IQR = 1‐9 y). Conclusions Regulatory authorities and drug manufacturers are likely to withdraw medicinal products quickly from the market when animal experiments suggest increased risks of cancers or congenital malformations. Human studies are seldom conducted when harms are suspected in animals. Future research should explore better methods of extrapolating harms data from animal research to humans.